Number of Doses of Systemic Antibiotic Prophylaxis May Be Reduced in Cemented Primary Knee Arthroplasty Irrespective of Use of Antibiotic in the Cement: A Multiregistry-Based Meta-Analysis - Tesfaye H. Leta, PhD; Richard N. Chang, MPH; Anne Marie Fenstad, MSc; Stein Atle Lie, PhD; Stein Håkon L. Lygre, PhD; Martin Lindberg-Larsen, PhD; Alma B. Pedersen, PhD; Olav Lutro, MD; Jinny Willis, PhD; Chris Frampton, PhD; Michael Wyatt, MD; Serban Dragosloveanu, MD; et al. (JBJS Open Access)
Background:. The use of systemic antibiotic prophylaxis (SAP) and antibiotic-loaded bone cement (ALBC) is the accepted practice to reduce the risk of periprosthetic joint infection (PJI) in primary total knee arthroplasty (pTKA). However, practice varies internationally. This study's primary aim was to compare the risk of PJI revision after pTKA with ALBC + SAP vs. plain bone cement (PBC) + SAP, and the secondary aim was to assess whether the risk of PJI revision varies with the number of SAP doses. Methods:. Cohort of 289,926 pTKAs for osteoarthritis from arthroplasty registries in Denmark, New Zealand, Norway, Romania, and United States registered from 2010 to 2020. One-year revision for PJI following pTKA with ALBC + SAP vs. PBC + SAP, and single vs. multiple SAP doses was compared. We computed cumulative percent revision (1 minus Kaplan-Meier) using distributed analysis method and adjusted hazard rate ratios (HRRs) using Cox regression analyses within each registry. Advanced distributed meta-analysis was performed to summarize HRRs from all countries. Results:. Among all pTKAs, 64.4% were performed with ALBC + SAP. Each registry reported a 1-year cumulative percent revision for PJI of <1.00% for both pTKAs with ALBC + SAP (0.34%-0.80%) and with PBC + SAP (0.54%-0.69%). The distributed meta-analysis showed HRR = 1.21; (95% confidence interval [CI], 0.79-1.87) for ALBC + SAP compared with PBC + SAP. Similar risk of PJI revision was observed between pTKAs with ALBC + single vs. multiple doses of SAP: 2 doses (0.95; 95% CI, 0.68-1.33), 3 doses (1.09; 95% CI, 0.64-1.87), and 4 doses (1.23; 95% CI, 0.69-2.21). Comparable results were found for the PBC + SAP group except for higher risk of PJI revision with 4 doses of SAP (2.74; 95% CI, 1.11-6.75). Conclusions:. ALBC and PBC entailed similar risk of PJI revision when patients received SAP in pTKA, regardless of number of SAP doses. ALBC or PBC used in combination with SAP in pTKAs, with one single preoperative dose of SAP may be sufficient without compromising the patient safety. Level of evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.